Complete remission of a high-risk, locally advanced cervical cancer with para-aortic lymph node metastases treated with first-line tislelizumab plus bevacizumab combined with chemotherapy followed by radiotherapy with maintenance therapy: a case report - Lang, Juan; Liu, Qianqian; Ji, Rong; Qiu, Miao; Wang, Siben; Liu, Qingmeng; Li, Dapeng; Chen, Ping; Xiong, Zhongkui (Frontiers in Immunology, 2025)
Newly diagnosed cervical cancer with metastatic para-aortic lymph node (PALN) involvement is associated with a significantly poor prognosis, with distant metastasis being the predominant pattern of treatment failure. The programmed cell death receptor-1 (PD-1) pathway has garnered considerable attention due to its role in enabling tumor cells to evade immune surveillance by eliciting the immune checkpoint response of T cells, rendering them highly refractory to conventional chemotherapy. The National Comprehensive Cancer Network (NCCN) guidelines currently recommend pembrolizumab for locally advanced cervical cancer patients positive for PD-L1 (CPS ≥1), as determined by an FDA-approved assay. Tislelizumab, an anti-PD-1 monoclonal IgG4 antibody, has been investigated in hematological malignancies and advanced solid tumors. Nevertheless, literature on regimens incorporating tislelizumab for the treatment of locally advanced cervical cancer is scarce. Herein, we present a case of a newly diagnosed high-risk, locally advanced cervical cancer patient with PALN metastases and low PD-L1 expression, treated with a combination of tislelizumab, bevacizumab, and a platinum-containing chemotherapy regimen followed by radiotherapy with maintenance therapy, resulting in a notable extension of progression-free survival.